Relationship between Taxpayers and Authorities against Tax Compliance during the Covid'19 Pandemic - Mangoting, Yenni; Junfandi, Jessica; Vania, Vania (Jurnal Dinamika Akuntansi, 2021)
Taxpayer compliance during the Covid 19 pandemic is an important issue in the relationship between taxpayers and tax authorities. This study was to identify taxpayer compliance behavior using factors, namely: procedural fairness, trust, and commitment. The commitment mediation effect was also tested in this study. Data were collected through questionnaire involving individual taxpayer respondents. A total of 102 collected questionnaires were analyzed using Partial Least Square (PLS). Procedural fairness in determining tax incentive policies during the Covid 19 pandemic is not enough to increase taxpayer compliance. The results of this study also prove that the commitment be a factor affecting tax compliance, either directly or indirectly. Result of mediation test prove that taxpayer’s commitment mediates the relationship of procedural justice on tax compliance. Similarly, commitment is a mediation in the relationship of trust on tax compliance. Therefore, it is important for the government and tax authorities to maintain the commitment of the taxpayer as part of a strategy to increase tax compliance and develop effective long-term relationships.